ABOUT OPTIMIZING OF INVESTMENT VOLUMES TO IMPROVE THE BASIC INDICATORS OF THE ENTERPRISE EFFECTIVENESS - Gasanov, Z. M. (Science and Transport Progress, 2015)
Purpose. Profit and profitability of any, including transport enterprises are the main economic indicators of the enterprise effectiveness. These indicators reflect the results and successful performance of the enterprise. On the other hand the enterprise effectiveness in the long term, assurance of rapid development and competitiveness is largely determined by the level of investment activity and the range of investment activity. The purpose of this study is the feasibility of the method to determine optimal investments volume for improving these or others (selectable by the management) principal economic indicators of the enterprise effectiveness. Methodology. The basis of the proposed methodology for determining the optimal investments volume is the theory of optimal control, in particular, the procedure of dynamic programming since a managed development process of the enterprise is a multiple stage. This procedure, using a phased plan, allows not only simplifying the solution of optimization problems, but also solving those, which are impossible to apply the methods of mathematical analysis. Findings. The expediency of performing the calculations to determine the optimal investments volume to ensure high rates of enterprise development was proved, it is a key to the effectiveness of the enterprise in the long term and it improves its competitiveness. Originality. It is shown that using methods of the optimum control theory one can calculate the minimum volume of capital investments for the improvement of economic indicators, which determine the enterprise effectiveness. The proposed method of calculation does not depend on the specific content of economic indicators. The effectiveness of this calculation method is demonstrated on a model example. Practical value. The proposed method of calculating the minimum volume of capital investments to improve the economic effectiveness of enterprises is quite simple, but at the same time enables, on the one hand, to determine priority directions of investment activity of the enterprise. On the other hand it improves the manageability and transparency of business enterprises, increases the head's confidence in the correctness of decisions.